Small cell neuroendocrine carcinoma of the uterine cervix (SCNEC): a case report and review - Puja Agung Antonius; Hariyono Winarto (Fakultas Kedokteran, Universitas Andalas, 2021)
Objective: Improving skill and knowledge to diagnose and manage a rare case of small cell neuroendocrine uterine cervical cancer Method: a Case report Result: A 51 years old, para 2, Indonesian woman with chief complaint post-coital vaginal bleeding. Gynecology examination revealed cervical exophytic fragile mass size 3x3x3,5 cm, easily bleeding, with a necrotic part, infiltrated both parametria but not reach the pelvic wall correspond to stage IIB. Initially, the histopathology result from punch biopsy was an adenocarcinoma well-differentiated, with no lymph vascular invasion, DD/ adenosquamous, neuroendocrine tumor. We did the histopathology review continued with immunohistochemistry examination. Immunohistochemistry result showed that although all the sample was not typical, immunohistochemical outward patterns can support morphological features of high-grade neuroendocrine carcinoma, small cell type. We proceed here for chemoradiation therapy. Conclusion: Small cell neuroendocrine carcinoma of the uterine cervix is a rare case. Histopathology and immunohistochemistry examination has an important role to develop the diagnosis. Although the prognosis is poor, adjuvant chemotherapy or chemoradiation was associated with improved survival in patients with advance staged. Keywords: SCNEC, immunohistochemistry, chemoradiation